Who owns the future? - Lanier, Jaron (New York Simon & Schuster, 2014)
Jaron Lanier is the father of virtual reality and one of the world?s most brilliant thinkers. Who Owns the Future? is his visionary reckoning with the most urgent economic and social trend of our age: the poisonous concentration of money and power in our digital networks.
Includes bibliographical references (pages 385-389) and index.
Keywords: Information technology--Economic aspects